Reversing the Question: Does Happiness Affect Consumption and Savings Behavior? - Cahit Guven (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
I examine the impact of happiness on consumption and savings behavior using data from the DNB Household Survey from the Netherlands and the German Socio-Economic Panel. Instrumenting individual happiness with regional sunshine, the results suggest that happier people save more, spend less, and have a lower marginal propensity to consume. Happier people take more time for making decisions and have more control over expenditures; they expect a longer life and (accordingly) seem more concerned about the future than the present; they also expect less inflation in the future.
Keywords: D3; D12; Q54; 330; happiness; savings; consumption; weather